ANTI OXIDANT ACTIVITY OF 96% ETHANOL EXTRACT Sargassum polycystum WITH DPPH (2,2-diphenyl-1-picrylhydrazyl) METHOD USING SPECTROPHOTOMETRIC UV-VIS - Dita Riwanti (JURNAL FARMASI DAN KESEHATAN INDONESIA, 2021)
S.polycystum is a plant that has potential as an antioxidant. The purpose of this study was to determine the antioxidant activity of the 96% ethanol extract of Sargassum polycystum. Sargassum polycystum was obtained from Jeruk Porot Hamlet, Cabbiya Village, Talango District, Sumenep Regency, Madura and extracted by maceration method using 96% ethanol as solvent. Furthermore, the antioxidant activity test of 96% ethanol extract of brown seaweed S. polycystum using concentrations of 156, 490, 501 and 840 mg/ml. The positive control used was ascorbic acid. Antioxidant activity test of 96% ethanol extract of S. polycystum was carried out using the DPPH (2,2-Diphenyl-1-picryl Hidrazil) method with UV-Vis spectrophotometry at a wavelength of 516 nm. The results showed that 96% ethanol extract of brown seaweed S. polycystum had antioxidant activity as indicated by an IC50 value of 492,9732 mg/ml, while vitamin C had an IC50 value of 2.9498 mg/ml so that 96% ethanol extract of Sargassum polycystum had weak antioxidant activity compared to ascorbic acid